Dying Oceans - Hogan, Paula Z (Milwaukee, Wisconsin Gareth Stevens, 1991)
Discusses the ecological balance of life in the world's oceans and how it is endangered by ocean pollution.
880L
Keywords: Marine pollution -- Evironmental aspects; Marine ecology; Pollution; Ecology; Conservation of natural resources